1990
DOI: 10.2165/00002018-199005040-00005
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Benefit Assessment of Amiodarone in the Treatment of Cardiac Arrhythmias

Abstract: Cardiac arrhythmias are a cause of significant morbidity and mortality in patients with cardiac disease, and thus represent a major management problem. The recognition that antiarrhythmic drugs have the potential to aggravate as well as to attenuate arrhythmias has prompted clinicians to reconsider treatment strategies and weight the benefits of treatment against the risks. In this context, amiodarone has emerged as an effective antiarrhythmic agent and when used at the lowest effective dose has an acceptable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
(65 reference statements)
1
9
0
3
Order By: Relevance
“…The mean concentration of amiodarone measured at 3 rnin after a 5 mg/ kg i.v. bolus injection was 4.1 f 1.5 mg/ L which is above the recommended human therapeutic range of 1-2.5 mg/ L (Counihan & McKenna 1990), but was similar to values obtained in man with the same weight adjusted i.v. dose (Andreasen et al 1981).…”
Section: Amiodaronesupporting
confidence: 83%
See 1 more Smart Citation
“…The mean concentration of amiodarone measured at 3 rnin after a 5 mg/ kg i.v. bolus injection was 4.1 f 1.5 mg/ L which is above the recommended human therapeutic range of 1-2.5 mg/ L (Counihan & McKenna 1990), but was similar to values obtained in man with the same weight adjusted i.v. dose (Andreasen et al 1981).…”
Section: Amiodaronesupporting
confidence: 83%
“…While this in part relates to concerns of lethal pro-arrhythmia associated with flecainide and other class lc drugs reported by the Cardiac Arrhythmia Suppression Trial (CAST) investigators (Echt et al 199 l), clinical experience with amiodarone and sotalol has been favourable, even in patients with severe left ventricular dysfunction (Amiodarone vs Sotalol Study Group 1989). While pro-arrhythmia may still occur with either of these two drugs, the incidence appears in general, to be less than that seen with class 1 antiarrhythmic drugs (Counihan & McKenna 1990).…”
Section: Discussionmentioning
confidence: 91%
“…This study demonstrated that a computerized tool in addition to collaboration among health care professionals was effective in increasing the percentage of patients receiving laboratory monitoring at initiation of therapy. 16 Multidisciplinary clinics have also been shown to have a higher adherence rate to amiodarone monitoring guidelines. 12 A specialized amiodarone clinic at the University of Illinois at Chicago provided care to its patients according to accepted monitoring guidelines, and increased adherence to guidelines from 23% prior to referral to 90% after clinic enrollment.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…If patients are not adequately monitored, the risks of amiodarone therapy may outweigh its beneficial antiarrhythmic effects. 15,16 Unfortunately, there are no additional outcome data associated with amiodarone monitoring guideline adherence. Yet, based on the frequency and seriousness of the adverse effects associated with the use of amiodarone, it seems likely that early detection through the recommended laboratory and radiographic assessments would result in improved patient outcomes.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…121 ] Hypothyroidism and hyperthyroidism may also occur with amiodarone, the former being found in I to 20% of elderly people taking this drug. [22,23] Those with an autoimmune thyroid disease (as evidenced by thyroid antibodies) appear to be at highest risk of hypo thyroidism. [24] Overt hyperthyroidism occurs in 1 to 5% of patients, often presenting with bodyweight loss and proximal myopathy.…”
Section: Drugs and Thyroid Dysfunctionmentioning
confidence: 99%